2014
DOI: 10.3892/ijo.2014.2609
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 downregulation by arsenic trioxide in lung adenocarcinoma

Abstract: Lung cancer is one of the most common cancers worldwide. Arsenic trioxide (ATO) has been approved by the US Food and Drug Administration for the treatment of acute promyelocytic leukemia. Nonetheless preliminary data have suggested potential activity of ATO in solid tumors including lung cancer. This study aimed to examine the underlying mechanisms of ATO in the treatment of lung adenocarcinoma. Using a panel of 7 lung adenocarcinoma cell lines, the effects of ATO treatment on cell viability, expression of E2F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…A previous clinical study demonstrated that patients with higher tumoral RRM1 expression exhibited a lower survival rate when treated with gemcitabine-based therapy (28). ATO downregulated RRM1 expression in lung adenocarcinoma, which may cause inhibition of DNA synthesis (11).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…A previous clinical study demonstrated that patients with higher tumoral RRM1 expression exhibited a lower survival rate when treated with gemcitabine-based therapy (28). ATO downregulated RRM1 expression in lung adenocarcinoma, which may cause inhibition of DNA synthesis (11).…”
Section: Discussionmentioning
confidence: 96%
“…Phosphatidylserine externalization has been observed in H841 SCLC cells (9) and H23 lung adenocarcinoma cells (10). Mitochondrial membrane depolarization is another indicator of apoptosis; it has been demonstrated that ATO can induce mitochondrial membrane depolarization in lung cancer cells (11). DNA damage is typically sensed at the G 1 /S checkpoint or G 2 /M checkpoint, leading to either DNA repair or cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations